Safety Analysis: Rooftop PV System Training Equipment - Rumokoy, Stieven Netanel; Warokka, Adriyan; Atmaja, I Gede Para; Gumilar, Lang-lang; Monika, Dezetty (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
The implementation of PV Rooftop Power Plant systems as an alternative energy source has become increasingly widespread. The growing use of these systems is accompanied by the need for skilled workers with competencies in their installation. To support the development of such competencies, various training equipment designs have been created to enhance workers' skills in rooftop PV installation. This article aims to evaluate Occupational Health and Safety (OHS) aspects in the designed rooftop PV training equipment. The methodology used in this research includes risk analysis through hazard identification, risk assessment, and mitigation recommendations. Data collection was conducted through a literature review related to OHS standards, direct observation of the equipment's use, and interviews with instructors and technicians involved. The research results show that the main risks include Falling Hazards, Electrical Hazards, Mechanical Hazards, Tripping or Snagging Hazards, and Ergonomic Hazards. Risk control measures were implemented by ensuring that the trainees understood work-related risks, using Personal Protective Equipment (PPE), and monitoring the condition of the work area and equipment.